HPCA confirmed as a genetic cause of DYT2‐like dystonia phenotype - Atasu, Burcu; Hanagasi, Hasmet; Bilgic, Basar; Pak, Meltem; Erginel‐Unaltuna, Nihan; Hauser, Ann‐Kathrin; Guven, Gamze; Simón‐Sánchez, Javier; Heutink, Peter; Gasser, Thomas; Lohmann, Ebba (Movement disorders, 2018)
Background: HPCA (hippocalcin) is one of the underlying genetic causes of autosomal‐recessively inherited forms of dystonia. Here, we describe two consanguineous Turkish DYT‐HPCA families carrying the novel HPCA mutations. Methods: After detailed clinical and neurological examination, whole‐exome sequencing was performed. Results: Whole‐exome sequencing analysis revealed two homozygous novel truncating mutations (p.W103* and p.P10PfsTer80) in the HPCA gene in two unrelated Turkish dystonia families presenting with complex dystonia. Conclusions: After identification of HPCA as a genetic cause of DYT‐HPCA‐like dystonia by Charlesworth et al, this is the second report in the scientific literature that describes dystonia families harboring HPCA mutations. Our findings confirm that HPCA leads to recessively inherited dystonia. © 2018 International Parkinson and Movement Disorder Society